Epidemiología de la Salmonelosis en Costa Rica I. Salmonelosis en porcinos - Cruz, Enrique de la (1958)
The high incidence of Salmonella in liver, spleen, mesenteric lymph node and feces of 150 apparently healthy pigs, for the local consumption of San José and surrounding areas is herewith discussed. The different serotypes that were isolated are reported with reference to their source of isolation and their frequency. Five of these serotypes had not yet been reported in hogs. For the first time in Costa Rica, the existence of 18 different serotypes is reported. The efficiency of tetrathionate broth using incubation periods of 24 to 48 hours is discussed. In a possible strain of S. san diego the presence of T1 antigen of Kauffmann is reported.